2019
DOI: 10.3390/ma13010031
|View full text |Cite
|
Sign up to set email alerts
|

Percussion Drilling Hole in Cu, Al, Ti and Ni Alloys Using Ultra-Short Pulsed Laser Ablation

Abstract: Comparative study on micro-deep hole drilling by picosecond ultra-short pulse laser in four metals, including copper, aluminum alloy, titanium alloy, and nickel alloy, was presented. Destructive testing was performed to measure the depth, shape, and side-wall morphology of micro-deep holes in this study. Diameters and depths of micro-deep holes in four metals ablated using the same processing parameters were compared. The multiple thresholds of metals had been calculated. Relationships between hole dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…By doubling the pulse energy, the drilling time decreases two orders of magnitude, while a further increase only results in a slight reduction in drilling time, which can be explained by the particle lubrication effect [ 23 ]. Furthermore, in this study, the repetition rate showed no significant influence on the heat accumulation between 200 kHz and 800 kHz, which agreed with Zhao et al [ 24 ]. Using pulse bursts, high ablation rates and a low surface roughness is possible [ 25 ].…”
Section: Introductionsupporting
confidence: 92%
“…By doubling the pulse energy, the drilling time decreases two orders of magnitude, while a further increase only results in a slight reduction in drilling time, which can be explained by the particle lubrication effect [ 23 ]. Furthermore, in this study, the repetition rate showed no significant influence on the heat accumulation between 200 kHz and 800 kHz, which agreed with Zhao et al [ 24 ]. Using pulse bursts, high ablation rates and a low surface roughness is possible [ 25 ].…”
Section: Introductionsupporting
confidence: 92%
“…In addition, due to the heat insulation of the paint and the Al 2 O 3 film, the temperature generated under the experimental conditions was even lower in comparison to the detected value. The substrate would not be damaged below its melting point [21,22], and its performance would not be influenced by the thermal effect from atmospheric pressure plasma [23].…”
Section: Mass Change and Sample Surface Temperature Analysismentioning
confidence: 99%
“…Laser modification is a new type of micro-machining surface texture technology that is different from traditional machining technology (Branemark et al, 2011). The thermal effect and photonic effect of the laser are used in laser modification to melt or vaporize the titanium-based implant surface to control the texture and chemical composition of the surface (Biswas et al, 2016;Zhao et al, 2019;Rafiee et al, 2020). Interference is a type of laser processing technology that uses two or more laser beams to form a periodic texture on the surface of the titanium-based implant (Hartjen et al, 2017;Zwahr et al, 2017).…”
Section: Laser Modificationmentioning
confidence: 99%